2007
DOI: 10.1016/j.cardiores.2006.11.031
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective effects of cerium oxide nanoparticles in a transgenic murine model of cardiomyopathy

Abstract: CeO2 nanoparticles protect against the progression of cardiac dysfunction and remodeling by attenuation of myocardial oxidative stress, ER stress, and inflammatory processes probably through their autoregenerative antioxidant properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
228
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 394 publications
(239 citation statements)
references
References 35 publications
11
228
0
Order By: Relevance
“…50 Finally, nanoceria might also be cardioprotective as intravenous injection of nanoceria attenuated left ventricle dysfunction and dilation of the heart of monocyte chemo-attractant protein 1 transgenic mice. 51 This effect was accompanied by a decrease in nitrotyrosine protein modification, inflammatory cytokines and ER stress gene expression. 51 Although many studies, including the present one, have reported antioxidant and cytoprotective effects of nanoceria, a few studies have provided conflicting data.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…50 Finally, nanoceria might also be cardioprotective as intravenous injection of nanoceria attenuated left ventricle dysfunction and dilation of the heart of monocyte chemo-attractant protein 1 transgenic mice. 51 This effect was accompanied by a decrease in nitrotyrosine protein modification, inflammatory cytokines and ER stress gene expression. 51 Although many studies, including the present one, have reported antioxidant and cytoprotective effects of nanoceria, a few studies have provided conflicting data.…”
Section: Discussionmentioning
confidence: 97%
“…51 This effect was accompanied by a decrease in nitrotyrosine protein modification, inflammatory cytokines and ER stress gene expression. 51 Although many studies, including the present one, have reported antioxidant and cytoprotective effects of nanoceria, a few studies have provided conflicting data. 37,[52][53][54] Differences in cell types, tissue context, environmental factors and nanoparticle synthesis and concentration might account for these conflicting findings.…”
Section: Discussionmentioning
confidence: 97%
“…ROS can be induced by several mechanisms, including (i) the interfernce with redox active proteins, (ii ) interaction with oxidative organelles such as the mitochondria, (iii) chemical reactions of the coating, reactive surface groups or ions leached from the NP surface in the acidic environment of endo-or lysosomes and (iv) by activation of several signalling pathways through interaction with cell surface receptors 28,40 . This paradigm does however not account for all NP: CeO2NP, for example, were found not to cause ROS induction but on the contrary even showed a protective effect against ROS damage in vivo as well as in vitro 51,52 . Furthermore, Gao et al…”
Section: Common Mechanisms Causing Nanotoxicitymentioning
confidence: 94%
“…84 The potential pharmacological activity of CeONP has also been evaluated. It was shown that CeONP could prevent retinal degeneration induced by intracellular peroxides 96 and could relieve the symptoms of ischemic stroke, 91 ischemic cardiomyopathy, 113 diabetes, 93 radiation-induced pneumonitis 105 and lupus 84 in animal models of disease. These effects mainly depended on the ROS scavenging ability of CeONP.…”
Section: The Toxicological Effects Of Ceonpmentioning
confidence: 99%